2020
DOI: 10.21203/rs.2.20847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surgical site infection following elective mesh repair of inguinal hernia: an analysis of risk factors

Abstract: Background: Surgical site infection (SSI) is a complication of mesh repair of inguinal hernia (IH) with an increase in length of stay and costs. We investigated both controllable and non-controllable risk factors for SSI following elective mesh repair of IH. Methods: A retrospective analysis was conducted of 1177 adult patients who underwent elective mesh repair of IH (not receiving antibiotic prophylaxis) from January 2010 to September 2019. Demographics, surgical variables and laboratory data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…A study conducted at The F Affiliated Hospital of Shantou University Medical College found that diabetes mellitus is one of the risk factors for SSI in inguinal hernia repair. 24 A systematic review showed a similar result, stating that diabetes mellitus is not only the independent risk factor for inguinal hernia repair but also other surgical procedural. 26 Diabetes mellitus causes a state of immunosuppression which puts the patients at a greater risk of infection, and microangiopathy, which leads to prolonged wound healing.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A study conducted at The F Affiliated Hospital of Shantou University Medical College found that diabetes mellitus is one of the risk factors for SSI in inguinal hernia repair. 24 A systematic review showed a similar result, stating that diabetes mellitus is not only the independent risk factor for inguinal hernia repair but also other surgical procedural. 26 Diabetes mellitus causes a state of immunosuppression which puts the patients at a greater risk of infection, and microangiopathy, which leads to prolonged wound healing.…”
Section: Discussionmentioning
confidence: 81%
“…Other studies stated that obesity increases SSI risk as it causes prolonged wound healing and decreases subcutaneous oxygen levels during the operation. 24,25 Such as the previous two factors, the immune system also serves as a bridge between diabetes mellitus and SSI incidence. A study conducted at The F Affiliated Hospital of Shantou University Medical College found that diabetes mellitus is one of the risk factors for SSI in inguinal hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…There are many influencing factors of surgical site infection. Some studies have listed the possible risk factors for surgical site infection in tension‐free hernia repair from two aspects: patient factors (age, nutritional status, history of diabetes, other organ infections, immunodeficiency, preoperative hospital stay, smoking history, obesity) and surgical factors (preoperative preparation, operation time, ventilation in the operating room, sterility of surgical instruments, surgical drainage and surgical skills); moreover, the researchers believed that the effect of improving surgical factors is much greater than that of the routine preventive application of antibiotics 57‐59 . From the subgroup analysis of the total incidence of surgical site infection in this meta‐analysis, it was found that seven studies in the past 10 years showed that the total incidence of surgical site infection in the AG was 3.7%, and that in the NAG was 3.2%.…”
Section: Discussionmentioning
confidence: 99%